Autosomal recessive woolly hair/hypotrichosis caused by LIPH mutations: a case report - Xie, Ying; Luo, Sha; Yang, Yumei; Zou, Xin; Lv, Shuying; Du, Meijiao; Xu, Yonglong; Song, Xiaojuan; Qi, Changjie; Li, Nuo; Yang, Dingquan (Frontiers in Medicine, 2025)
ObjectiveTo report the clinical characteristics of a case of Autosomal recessive woolly hair/ hypotrichosis(ARWH/HT, OMIM:278150/604379) in a child, analyze and identify the causative gene and mutation site. A review of related research at home and abroad was conducted to summarize the current progress in the diagnosis and treatment of ARWH.MethodsClinical data were collected, and exome sequencing was performed on blood samples from the patient and parents to screen for mutations. Sanger sequencing validated suspected pathogenic variants. A summary analysis of previously published woolly hair cases was also conducted.ResultsThe family was found to have mutations in the LIPH gene, with the patient’s sample showing two heterozygous mutations: c.1101del (maternal) and c.736 T > A (paternal). These compound heterozygous mutations are responsible for the ARWH phenotype.ConclusionThe compound heterozygous mutations c.1101del and c.736 T > A in the LIPH gene are the pathogenic mutations causing the clinical phenotype of autosomal recessive woolly hair in the child. The c.1101del mutation is a newly discovered frameshift mutation, enriching the mutation spectrum of LIPH-associated autosomal recessive woolly hair with hypotrichosis.